Corrosion Inhibition of Low Carbon Steel in Different HCl Concentrations by Phenythiourea - S. Yaro, Aprael; A . Rashed, Nashwan; S. Abdul-Hassan, Ahmed (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Phenylthiourea (PHTU),was tested as inhibitor for the corrosion of low carbon steel in different HCI acid concentration by mass loss ,and polarization measurements .it was found that (PHTU) is a good inhibitor for the corrosion of low carbon steel in 1,3,and 5N HCI solution ,and its inhibition efficiency (0) increases with its concentration and attains approximately 97% at l g/I .polarization curves indicate that (PHTU) acts as an anodic type inhibitor .the inhibitor was adsorbed on the low carbon steel surface according to the Langmuir adsorption isotherm model. Results show that the rate of corrosion of low carbon steel increased with increasing temperature over the range 30-60°C, both in the presence of inhibitor and its absence .it was found also that the inhibiting effect of the inhibitor is generally acid concentration independent.